PENGARUH PERMAINAN TEBAK GAMBAR TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN DI TK AISYIYAH BUSTANUL ATFHAL TANJUNG BONAI KABUPATEN TANAH DATAR PROVINSI SUMATERA BARAT - Vortuna, Dewi; Indarto, Wusono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aim to know influence of the pictures guessing game to ability the speak of children aged 5-6 years in TK Aisyiyah Bustanul Atfhal Tanjung Bonai, Tanah Datar, West Sumatra. This study was an experimental study which use one group design with pretest, posttest, and observation sheet about the childâs ability to speak. The sample used in this study are19 people. The data collection techniques were used that observation. Data were analyzed using t-test and SPSS 21.0. The hypothesis of this study is the significant influence on the speak of children after we apply the pictures guessing game to them. To find out the hypothesis is accepted or rejected based on the data SPSS 21.0 viewable thitung ê17.066 greater than ttable ê 1.734 (17.066> 1.734). Thus Ho is rejected and Ha is accepted. It means that there are the significant influnce on the speak of children after they play the game. The results also see the influence of the picture guessing game against the speech of children aged 5-6 years. It can be seen from the value of the correlation coefficient (r) as big as 0.694 with a coefficient of determination (r2) as big as 0.694 x 0.694 = 0.481 means the picture guessing game influence on the ability to speak is at 48.16% which is the strong category.Key Words: Speak, Picture Guessing Game